Climate change mitigation and adaptation through livestock waste management - E. Frimawaty; A. Ilmika; N. Sakina; J. Mustabi (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Farmer characteristics are recognized in this study. The characteristics, perceptions, willingness to adopt climate change mitigation, and awareness of livestock farmers toward livestock waste management are the main points for determining appropriate climate mitigation rules.METHODS: This study was conducted in Enrekang and Barru Regencies of South Sulawesi. International Business Machines - Statistical Package for the Social Sciences 27 was used for this study. In descriptive statistics, data were compiled, and the age, long husbandry experiences (year), number of family member, number of farming assistant, gender, education, farmer group participation status, side job, type of business, cattle ownership status, number of cattle (head), and weight total of cattle’s manure (kilogram per day) were examined qualitatively. A chi-square test was used to compare the experimental results (perception and knowledge of livestock manure management) with practical livestock manure management.FINDING: This study found that the average age of farmers in the study area is 45 and 11.2 percent received have high formal education level from a university. Most of the cattle are male at 86.7 percent. Poor manure management system at 76.30 percent manure un-managed and un-appropriate farmer groups with more than 60 percent of the farmers un-joined farmer’s group. Almost 50 percent of the cattle farmers are willing to learn manure management. Nevertheless, this study found that the respondents’ knowledge and practical manure management, as well as the respondents’ knowledge (0.837) and perception (0.343) of practical manure management, do not have any significant connection.CONCLUSION: This study determines the full condition of cattle farmers in Barru and Enrekang Regencies. Barriers include low level of education, age of farmers, lack of manure management, and lack of willingness to join farmers group. Nevertheless, drivers, such as willingness to adopt manure management and high levels of experience in cattle farming,  were also found. Enriching the knowledge and perception of farmers is essential in managing livestock wastes to mitigateof climate change.